The Role of Urokinase-Type Plasminogen Activator (UPA) Level and Some Biochemical Parameters in Iraqi Hemodialysis Patients - AL-Sudani, Fatima; Al-Shammaa, Nawal M.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The term end-stage kidney disease (ESKD) is often used to describe people who have the last stage of chronic kidney disease (CKD) and are undergoing dialysis or a kidney transplant for treatment. Hemodialysis (HD) is the most prevalent technique that is utilized to eliminate waste and other hazardous chemicals from the body. The study aims to assess the role of serum Urokinase plasminogen activator (UPA) levels among Iraqi hemodialysis patients. The study encompassed 50 patients aged 40–74 years (21 males and 29 females) admitted to the Iraqi dialysis center at Baghdad Teaching Hospital for the period from October 2022 to February 2023. They were diagnosed based on previous medical reports and laboratory and clinical tests by a consultant nephrologist. UPA, liver enzymes, blood urea, creatinine, albumin, total protein, sodium, potassium, total Ca, and PO4 levels were determined. This study demonstrates higher levels of UPA in HD patients with ESKD and correlates with ALP; also, UPA can be considered a good marker for the prevention of the development of kidney fibrosis.